An improved performance-based plastic design method for seismic resilient fused high-rise buildings. (15th November 2019) - Zhai, Zhipeng; Guo, Wei; Li, Yaozhuang; Yu, Zhiwu; Cao, Hongpeng; Bu, Dan
Highlights: An improved PBPD method considering high-mode effect and post-yield stiffness is proposed. The performance-based design and application of a novel EDC-MF system is discussed. The proposed design procedure can achieve the target RDRs, pre-selected yielding mechanism and multiple performance objectives. The designed EDC-MF system has good seismic performance against strong ground motions. Abstract: The performance-based plastic design (PBPD) method generally relies on the nonlinear response of equivalent elastic-perfectly-plastic single degree of freedom system. It usually cannot achieve the design of three performance objectives simultaneously and may not consider the high mode effect of structure, which is significant for high-rise building. In this paper, a trilinear force-displacement model indicating three prescribed performance objectives at three seismic hazard levels is adopted to improve the PBPD method. The proposed improved PBPD method is derived based on multiple degrees of freedom system, while the high-mode effect and post-yield stiffness of the structure is considered. It can be used for designing seismic resilient fused high-rise buildings. A novel dual system composed of steel energy-dissipative column (EDC) and moment resisting frame (MF) is employed for application of the proposed method. This dual system has its fuse members decoupled from the gravity-resisting system, and the performance-based design of this system is discussed as well as its application for high-rise buildings. To demonstrate the effectiveness of the proposed method, a 20-story EDC-MF structure system is designed using the improved PBPD method. A detailed numerical model of the designed EDC-MF system is then built, and nonlinear dynamic response analyses at different seismic intensities are performed to verify the actual structure performance. Results show that the designed structure can achieve the prescribed yielding mechanism and performance objectives at three seismic hazard levels, and the EDC-MF system can be effectively applied to high-rise building as a seismic resilient fused structure.